1985
DOI: 10.1042/bj2290751
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of degradation process of sucrase-isomaltase in jejunum of adult rats

Abstract: To evaluate degradation processes of sucrase-isomaltase in adult rat jejunum, we determined enzymic activity of sucrase and isomaltase and compared it with the amount of immunoreactive sucrase-isomaltase. In rats fed or starved for 18h, killed at 10:00 h or 22:00 h, sucrase activity (expressed on the basis of total protein or of immunoreactive sucrase-isomaltase) was significantly (P less than 0.02) lower in the lower jejunum than in the upper jejunum; isomaltase activity was similar in both segments. Crossed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 25 publications
7
26
0
Order By: Relevance
“…Because sucrase-isomaltase is known to be coded in a single gene (20) and synthesized as a single polypeptide of pro-sucrase-isomaltase (21), the alteration of sucrase to isomaltase activity ratio suggested that sucrase isomaltase was posttranslationally modified by the dietary manipulation. Degrada tion of sucrase-isomaltase was suggested to occur first on the sucrase subunit in the intestinal microvillar membranes (22,23). Therefore, it seems most likely that degradation of sucrase-isomaltase was enhanced in the rats fed the high-fat diet.…”
Section: And Discussionmentioning
confidence: 99%
“…Because sucrase-isomaltase is known to be coded in a single gene (20) and synthesized as a single polypeptide of pro-sucrase-isomaltase (21), the alteration of sucrase to isomaltase activity ratio suggested that sucrase isomaltase was posttranslationally modified by the dietary manipulation. Degrada tion of sucrase-isomaltase was suggested to occur first on the sucrase subunit in the intestinal microvillar membranes (22,23). Therefore, it seems most likely that degradation of sucrase-isomaltase was enhanced in the rats fed the high-fat diet.…”
Section: And Discussionmentioning
confidence: 99%
“…1). It has been demonstrated that this column efficiently separates sucrose-isomaltase complex and its degradation product, i.e., isomaltase monomer (6,15). The fractions containing sucrase-isomaltase and the fractions containing isomaltase monomer were denoted as peak II and peak III, respectively.…”
Section: ) Identification Of Disaccharidases Responsible For Hydrolymentioning
confidence: 99%
“…As mentioned above, cholestyramine and bile diversion lowered the activities of luminal trypsin and chymotrypsin probably by means of decreased abundance of luminal bile acids. Because the sucrase-active site is degraded by the action of pancreatic proteinases (7,8), it is possible that the increase in sucrase activity with cholestyramine or bile diversion might result from the decrease in degradation by the luminal proteinases. The activity of alkaline phosphatase was increased with cholestyramine but not with bile diversion, so this enzyme may be affected by other factors than the luminal bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a number of studies showed that some enzymes presented in the intestinal brush border membrane were influenced by the luminal factors (4-11). Goda and Koldovsky (7) reported that the sucrase-active site of sucrase-isomaltase in the small intestine of rat is degraded by the action of pancreatic proteinases. Goda et al (8) showed that the intake of a high-protein, low-carbohydrate diet accelerated the degradation of sucrase-isomaltase by means of the increase of luminal pancreatic proteinases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation